Mini and Micro LNG for Commercialization of Small Volumes of Associated Gas - Tractebel Engineering (World Bank, Washington, DC, 2017)
While the LNG industry has traditionally focused primarily on development of ever increasing plant capacities, the maturity of the technology has allowed development of technologies applicable for small volumes to be competitive and potentially economically attractive. The main challenge for small scale LNG applications is therefore not technical but economic. Mini/micro LNG facilities currently mainly consist of LNG liquefaction plants supplying LNG satellite stations with annual LNG volumes up to 0.2 mtpa. As an indication, these LNG quantities correspond to the yearly LNG demand for a power plant up to approximately 100 MW. The mini-LNG chain is virtually identical to the conventional LNG chain, differing only in scale. One difference is that for small gas volumes, LNG transport is feasible using trucks (onshore) or barges (offshore) rather than large marine carriers. While the purpose of this study is not provide a tool to estimate the cost of the chain but to provide an overview of the main elements that should be taken into consideration when evaluating the potential for specific projects, it is important to give some indication of potential cost (capital and operating) of an LNG chain.